Influence of Shaking Sequence on Liquefaction Resistance and Shear Modulus of Sand Through Shaking Table Tests - Roohollah Farzalizadeh; Abdolreza Osouli; Prabir K. Kolay (Geosciences, 2025)
Case histories have shown that the liquefaction behavior of soils can differ depending on the pre-seismic history of sites. Assessing the shear modulus in soils subjected to seismic events is critical for advancing the fundamental understanding of soil behavior and enhancing the accuracy of soil modeling applications. This paper aims to study the effect of small and large pre-shaking sequences on the liquefaction resistance and shear modulus of sand through shaking table tests. The experimental results indicated that small shakings increase liquefaction resistance and shear modulus. Although large shakings leading to liquefaction cause significant densification, they significantly reduce the liquefaction resistance and shear modulus of sand at shallow depths due to the upward water flow during excess pore water pressure dissipation. The high upward flow of water during liquefaction changes the soil structure and increases the horizontal displacement of densified soil in the subsequent shaking. The amplification factor of acceleration was found to be primarily influenced by the excess pore water pressure generated in the soil instead of its relative density at the start of shaking. This paper presents the variations in Ru with shear strain and the relationship between a normalized shear modulus and shear strain considering the pre-shaking history of sand for shallow depths.